2021
DOI: 10.1039/d0nj05603k
|View full text |Cite
|
Sign up to set email alerts
|

Molecular design principles of ionic liquids with a sulfonyl fluoride moiety

Abstract: New family of SO2F-functionalized ionic liquids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Changing from an imidazolium to a pyridinium cation generally raises T g /T m and, as expected, it was found that a protic amino group pendant on the pyridinium cation brings about a dramatic increase in T m . 34 We note that hydrogen bonding is not singularly responsible for 9 and 10 having higher T m values than 1 and 2, but rather the observed ΔT m likely reflects a net effect accounting also for the impact of increased cation symmetry. Following on previous studies evaluating the impact of the dipole on physicochemical properties of the ILs, we performed quantum chemical simulations in order to evaluate the electronic environment associated with the different substitutions on the rings.…”
Section: Structure−physicochemical Property Relationshipsmentioning
confidence: 72%
“…Changing from an imidazolium to a pyridinium cation generally raises T g /T m and, as expected, it was found that a protic amino group pendant on the pyridinium cation brings about a dramatic increase in T m . 34 We note that hydrogen bonding is not singularly responsible for 9 and 10 having higher T m values than 1 and 2, but rather the observed ΔT m likely reflects a net effect accounting also for the impact of increased cation symmetry. Following on previous studies evaluating the impact of the dipole on physicochemical properties of the ILs, we performed quantum chemical simulations in order to evaluate the electronic environment associated with the different substitutions on the rings.…”
Section: Structure−physicochemical Property Relationshipsmentioning
confidence: 72%
“…We previously noted that strategically placed side-chain branching poses a substantial depressive effect on the melting point ( T m ) values of ILs in which they are incorporated. Encouraged by these results, we speculated that using a mixture of hydrophobic amino acids as the basis for our anions might provide a workable degree of fluidity (viz. reducing melting point and viscosity) on the part of the IL, thus improving the efficiency of the resulting salts to chemisorb CO 2 from air.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, 4-(2aminoethyl)benzenesulfonyl fluoride (AEBSF) hydrochloride was reported to improve the crystallisation quality and phase stability of formamidinium lead iodide (FAPbI3) perovskite, which is used in solar cells, thus increasing the power conversion efficiency of the FAPbI3-based photovoltaic 162 . In 2021, Hillesheim and Mirjafari reported a series of sulfonyl fluoride-containing task-specific ionic liquids (ILs), which demonstrated good thermodynamic stability against hydrolysis and thermolysis, and could be prepared in multigram scale with minimal purification 163 . Given the established biocompatibility of sulfonyl fluorides, the preparation of ILs of this type which also incorporate components of active pharmaceutical ingredients are expected to find biological applications.…”
Section: Sufex In Materials Chemistrymentioning
confidence: 99%